Optimizing Artificial Intelligence (AI) as a Learning Media for Islamic Religious Education in the Society Era 5.0 - Wanseli Hidayatur Rohma; Imam Machfudi; Fathiyaturrohmah Fathiyaturrohmah (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2026)
This study aims to examine the optimization of artificial intelligence (AI) as a learning medium for Islamic Religious Education (IRE) through the use of the Quizizz AI platform at MTs Sunan Kalijaga Senduro, Lumajang Regency. This research employed a descriptive qualitative approach with a field research design. Data were collected through in-depth interviews, classroom observations, and document analysis involving IRE teachers and students of grades VIII and IX. Data analysis was conducted using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The findings indicate that the use of Quizizz AI as a formative assessment medium enhances the effectiveness of IRE learning evaluation and increases students’ engagement and learning motivation. The platform enables teachers to conduct assessments more efficiently, objectively, and systematically through automated feedback that supports instructional follow-up. However, several challenges were identified, particularly related to teachers’ limited digital literacy and the technical constraints of the internet infrastructure. This study concludes that Quizizz AI has significant potential as an adaptive and innovative assessment medium for Islamic Religious Education in the Society 5.0 era, provided that it is supported by continuous teacher training, supportive madrasa policies, and ethical technology use grounded in Islamic values